Propagation of Waves in Thin Nanorod With the Effect of Thermal Field - Priyanka, A. Siva; Amuthalakshmi, A. (Communications in Mathematics and Applications, 2024)
In this paper, thermal response for the propagation of waves in thin nanorod is studied with the Timoshenko beam theory. The important role for vibrational analysis of the rod and characteristics of the flexural waves is discussed. Numerical calculations are derived and the scattered relations between the wavenumber and wave velocities are computed.